(untitled) (Indianapolis, IN, 2005)
SQL functions are special commands for manipulating data. The international SQL standard defines many functions implemented by all major RDBMS vendors. This comprehensive SQL functions reference enables you to quickly master SQL function data manipulation in any database. First, the book presents the basics you need to use standard SQL functions with any database. Then the expert authors take you into the core reference material for built-in and user-defined SQL functions in each major RDBMS product. Packed with examples, you'll immediately learn to apply standard functions and extend your power with functions you define.
Keywords: Sql (computer program language)